04.11 Hypoxia and rheumatoid phenotype prevent synovial fibroblasts from suppressing t helper cell proliferation through ido1-mediated tryptophan metabolism. (1st March 2017) - Kaul, Nathalie-Christin; Mohapatra, Soumya; Adam, Isabell; Krienke, Stefan; Tucher, Christine; Opitz, Christiane; Lorenz, Hanns-Martin; Tykocinski, Lars
Abstract : Background: The development of rheumatoid arthritis (RA) is linked to changes in synovial fibroblasts' (SF) phenotype and local infiltration of immune cells. In addition, hypoxic conditions are detected within the inflamed joints of RA patients. The oxygen level in RA joints is only about 22, 5mmHg corresponding to ambient oxygen tensions of 3.2%. Right now there is not much known about the effect of hypoxia on the interaction between fibroblasts and immune cells and its implications on the pathophysiology of RA. Materials and methods: SF from synovectomy tissues of patients with osteoarthritis (OA) and RA were cultured in vitro . CD4-positive T cells were isolated from peripheral blood. The interaction between both cell types was examined through in vitro co-cultures both under normoxic and hypoxic (3%O2 ) conditions. The proliferation of Th cells was detected by PKH26 labelling and flow cytometry. Secretion of cytokines was quantified by ELISA. Indoleamine 2, 3-dioxygenase 1 (IDO1) expression was measured by real-time PCR and Western Blot. Tryptophan amounts were detected by HPLC. IDO1 activity was blocked by 1-l-methyl-tryprophan (1-L-MT). Results: SF strongly inhibit the proliferation of co-cultured Th cells. However, RASF have a significantly weaker T cell suppressive capacity compared to OASF. The inhibition of T cell proliferation – both via OASF and RASF - is diminished through hypoxia. Blockade of IDO1 completely restores Th cell proliferation, indicating that the suppression of Th cell proliferation by SF is mediated by tryptophan metabolism. Accordingly, in the supernatants of co-cultures with OASF, the amount of tryptophan is highly reduced, whereas in co-cultures with RASF more tryptophan is left. Under hypoxic conditions the tryptophan metabolism as well as the mRNA expression and protein levels of IDO1 are reduced. IFNγ levels are decreased, IL-6 and IL-8 expression are unaffected by hypoxia. Conclusions: The suppression of activated T cells by SF through tryptophan metabolism may participate in the prevention of inappropriate T cell responses under normal conditions. The inferior efficiency of RASF to restrict T cell proliferation and the reduced tryptophan metabolism under hypoxia likely support the development of synovitis in RA.